Testosterone deficiency impairs cardiac interfibrillar mitochondrial function and myocardial contractility while inducing oxidative stress - do Val Lima, Patrícia Ribeiro; Ronconi, Karoline Sousa; Morra, Elis Aguiar; Rodrigues, Paula Lopes; Ávila, Renata Andrade; Merlo, Eduardo; Graceli, Jones B.; Simões, Maylla Ronacher; Stefanon, Ivanita; Ribeiro Júnior, Rogério Faustino (Frontiers in Endocrinology, 2023)
Considering the intimate connection between oxidative metabolism and myocardial contractility, we determined the effects of testosterone deficiency on the two spatially distinct subpopulations of cardiac mitochondria, subsarcolemmal (SSM) and interfibrillar (IFM). We assessed cardiac contractility and the function and structure of SSM and IFM after 12 weeks of testosterone deficiency. Results show that low testosterone reduced myocardial contractility. Orchidectomy increased total left ventricular mitochondrial protein in the SSM, but not in IFM. The membrane potential, size and internal complexity in the IFM after orchidectomy were higher compared to the SHAM group. However, the rate of oxidative phosphorylation with all substrates in the IFM after orchidectomy was lower compared to the SHAM group.Testosterone replacement restored these changes. In the testosterone-deficient SSM group, oxidative phosphorylation was decreased with palmitoyl-L-carnitine as substrate; however, the mitochondrial calcium retention capacity in IFM was increased. There was no difference in swelling of the mitochondria in either group.These changes in IFM were followed by a reduction in phosphorylated form of AMPactivated protein kinase (p-AMPK-α), peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) translocation to mitochondria and decreased mitochondrial transcription factor A (TFAM). Testosterone deficiency increased NADPH oxidase (NOX), angiotensin converting enzyme (ACE) protein expression and reduced mitochondrial antioxidant proteins such as manganese superoxide dismutase (Mn-SOD) and catalase in the IFM. Treatment with apocynin (1.5 mM in drinking water) normalized myocardial contractility and interfibrillar mitochondrial function in the testosterone depleted animals. In conclusion, our findings demonstrate that testosterone deficiency leads to reduced myocardial contractility and impaired cardiac interfibrillar mitochondrial function. Our data suggest the 3 involvement of reactive oxygen species, with a possibility of NOX as an enzymatic source.